ChemInform Abstract: Amino Acid Salt Catalyzed Asymmetric Synthesis of 1, 2‐Diols with a Quaternary Carbon Center. Issue 7 (January 2016) - Wu, Quanquan; Liu, Shulei; Wang, Fangyuan; Li, Qingqing; Cheng, Kangli; Li, Juan; Jiang, Jun
Abstract: The efficient reaction between hydroxyacetone and aryl substituted α‐keto esters provides the products in high yields and with high dia‐ and enantioselectivity.